Fractalkine shedding is mediated by p38 and the ADAM10 protease under pro-inflammatory conditions in human astrocytes - DEV, KUMLESH (My University, 2016)
Check TCD e-journals(opens in a new window)|View at Publisher| RIS export | Download | Add to List | More... Journal of Neuroinflammation Volume 13, Issue 1, February 08, 2016, Article number 31 Open Access The dual S1PR1/S1PR5 drug BAF312 (Siponimod) attenuates demyelination in organotypic slice cultures (Article) O'Sullivan, C.a, Schubart, A.b, Mir, A.K.b, Dev, K.K.a a Trinity College, Drug Development, School of Medicine, Dublin, Ireland b Novartis Institutes for BioMedical Research, Novartis Pharma AG, Basel, Switzerland View references (42) Abstract Background: BAF312 (Siponimod) is a dual agonist at the sphingosine-1 phosphate receptors, S1PR1 and S1PR5. This drug is currently undergoing clinical trials for the treatment of secondary progressive multiple sclerosis (MS). Here, we investigated the effects of BAF312 on isolated astrocyte and microglia cultures as well as in slice culture models of demyelination. Methods: Mouse and human astrocytes were treated with S1PR modulators and changes in the levels of pERK, pAkt, and calcium signalling as well as S1PR1 internalization and cytokine levels was investigated using Western blotting, immunochemistry, ELISA and confocal microscopy. Organotypic slice cultures were prepared from the cerebellum of 10-day-old mice and treated with lysophosphatidylcholine (LPC), psychosine and/or S1PR modulators, and changes in myelination states were measured by fluorescence of myelin basic protein and neurofilament H. Results: BAF312 treatment of human and mouse astrocytes activated pERK, pAKT and Ca2+ signalling as well as inducing S1PR1 internalization. Notably, activation of S1PR1 increased pERK and pAKT in mouse astrocytes while both S1PR1 and S1PR3 equally increased pERK and pAKT in human astrocytes, suggesting that the coupling of S1PR1 and S1PR3 to pERK and pAKT differ in mouse and human astrocytes. We also observed that BAF312 moderately attenuated lipopolysaccharide (LPS)- or TNFaα/IL17-induced levels of IL6 in both astrocyte and microglia cell cultures. In organotypic slice cultures, BAF312 reduced LPC-induced levels of IL6 and attenuated LPC-mediated demyelination. We have shown previously that the toxic lipid metabolite psychosine induces demyelination in organotypic slice cultures, without altering the levels of cytokines, such as IL6. Importantly, psychosine-induced demyelination was also attenuated by BAF312. Conclusions: Overall, this study suggests that BAF312 can modulate glial cell function and attenuate demyelination, highlighting this drug as a further potential therapy in demyelinating disorders, beyond MS.
PUBLISHED